Forward-looking decision making: dynamic programming models applied to health, risk, employment, and financial stability (the gorman lectures in economics) - Hall, Robert E (The Gorman Lectures in Economics, 2010)
Individuals and families make key decisions that impact many aspects of financial stability and determine the future of the economy. These decisions involve balancing current sacrifice against future benefits. People have to decide how much to invest in health care, exercise, their diet, and insurance. They must decide how much debt to take on, and how much to save. And they make choices about jobs that determine employment and unemployment levels. Forward-Looking Decision Making is about modeling this individual or family-based decision making using an optimizing dynamic programming model.